(untitled) (The Pakistan Development Review, 1994)
The Structural Adjustment and Stabilisation Programmes of the IMF, World Bank and other international financial institutions for Pakistan have called for a reduction in the fiscal deficit, a restricted role of government in the economy, rationalisation of tax structure, removal of subsidies on consumption and production, etc. with a view to fostering efficiency, higher levels of output, stability of prices, etc. To what extent these objectives have been realised has rarely been examined. Firoze (1986) is probably the only exception who concludes that because of the structural weakness and adherence to just financial criteria these programmes have resulted in accumulating structural problems rather than alleviating them. These programmes also have significant implications for employment, poverty and income distribution.